Answer:
f(x) × g(x) = 15x^6 - 6x^4
Step-by-step explanation:
hello :
f(x) = 5x^3 -2x and g(x) =3x^3.
f(x) × g(x) = 3x^3(5x^3 -2x) = 15x^6 - 6x^4
AnsAnswerwer:
sorry i can't help without the picture of the problem
Step-by-step explanation:
Multiply the first equation with (-1)
you should get this
-6r + 3t = -6
6r + 8t = -16
start to eliminate
11t = -22
divide by 11
t = -2
substitute
6r - 3(-2) = 6
6r + 6 = 6
6r = 6 - 6
6r = 0
r=0
Answer: You would put the 35° and the 4x+7° equal to each other.
Step-by-step explanation:
1. 4x+7=35
2. 4x+7=35 -> Subtract 7 from the positive 7 and the 35
-7 -7
3. 4x=28 -> Divide 4x and 28
4. x=7
Answer:
So, we conclude that the best estimate for the difference in the proportion of smokers is 4.4%.
Step-by-step explanation:
We know that 27 of the 193 males in the sample smoke while 16 of the 169 females in the sample smoke.
We have the following proportion:
So we get that 13.9% of men smoke.
We have the following proportion:
So we get that 9.5% of women smoke.
We get: 13.9%-9.5%=4.4%.
So, we conclude that the best estimate for the difference in the proportion of smokers is 4.4%.